How lifespan associated genes modulate aging changes: lessons from analysis of longitudinal data - Yashin, Anatoliy I.; Arbeev, Konstantin G.; Wu, Deqing; Arbeeva, Liubov S.; Kulminski, Alexander; Akushevich, Igor; Culminskaya, Irina; Stallard, Eric; Ukraintseva, Svetlana (Frontiers in Genetics, 2013)
Background and Objective. The influence of genes on human lifespan is mediated by biological processes that characterize body’s functioning. The age trajectories of these processes contain important information about mechanisms linking aging, health and lifespan. The objective of this paper is to investigate regularities of aging changes in different groups of individuals, including individuals with different genetic background, as well as their connections with health and lifespan. Data and Method. To reach this objective we used longitudinal data on four physiological variables, information about health and lifespan collected in the Framingham Heart Study, data on longevity alleles detected in earlier study, as well as methods of statistical modeling. Results. We found that phenotypes of exceptional longevity and health are linked to distinct types of changes in physiological indices during aging. We also found that components of aging changes differ in groups of individuals with different genetic background. Conclusions. These results suggest that factors responsible for exceptional longevity and health are not necessary the same, and that postponing aging changes is associated with extreme longevity. The genetic factors which increase lifespan are associated with physiological changes typical of healthy and long-living individuals, smaller mortality risks from cancer and CVD and better estimates of adaptive capacity in statistical modeling. This indicates that extreme longevity and health related traits are likely to be less heterogeneous phenotypes than lifespan, and studying these phenotypes separately from lifespan may provide additional information about mechanisms of human aging and its relation to chronic diseases and lifespan.